Multiple material additive manufacturing platform - Tan, Jie Lun (Nanyang Technological University, 2020)
Additive manufacturing (AM) has brought about many benefits in the world of manufacturing. Its ability to construct parts with complex geometries, which was once impossible using the traditional manufacturing methods, allows for a great degree of design freedom. Selective laser melting (SLM) is an AM technique which uses a powder-bed platform to build up parts layer by layer. The built parts are able to achieve near full densities compared to the traditional manufacturing methods. SLM uses a laser beam to fully melt the powder on the top layer, after which a new layer of powder will be deposited over the previous layer. Current SLM machines uses single material for each print job due to their unique material deposition method. Unfortunately, the use of single material in each print job greatly limits the capabilities of SLM in expanding beyond their current applications since the mechanical properties are limited to the material used in the print. By allowing multiple materials in SLM, the desired mechanical properties can be varied within the part. Numerical modelling has been used to study laser melting processes such as laser welding and SLM. The main advantages of using numerical modelling is that it allows numerous simulations to be conducted simultaneously and avoids material wastages. The results from the simulations were in agreement with the experiments. The use of simulations can provide deeper insights on the behaviour of the molten metals during melting and solidification. However, there is currently no model for multi-material SLM process. Therefore, a numerical model for multi-material in SLM is developed in this work. Firstly, discrete element method (DEM) was used to model the powder bed. The powders were released from a height and allowed to fall and scatter randomly, similar to the recoating mechanism in SLM process. A moving laser source was adopted in the model to study the thermal conductivities of single and multi-material powder beds. Next, a computational fluid dynamics (CFD) approach was used to model the melting and solidification process in the SLM. Information of the powder bed generated using DEM was imported to the CFD solver where a Gaussian heat source is used to melt the powder into a molten pool and the molten metal was allowed to solidify. The dimensions of the molten pool in the model was compared to those measured in experiments in literature to compare the accuracy of the model. The model was used to study the formation of porosities in the SLM process and its relationship with energy density. Two types of porosities were observed. Lack of fusion porosities were formed when low energy density parameters were used. Incomplete melting of the powders resulted in gas trapped between powder particles. Keyhole porosities were observed when high energy density parameters were applied on the powder bed. A deep and unstable keyhole led to the collapse of the keyhole, trapping gas within the molten metal. Lastly, a multi-material model was built on a modified set of governing equations from the single material model. An additional phase was added to represent the second metal. The material properties of the mixture of both metals was calculated using a volume weighted average method. Ti6Al4V powder was deposited on a SS316L baseplate and the laser source scanned across the powder bed. Different values of interfacial tensions between the two materials were used to study their resultant effects on the material mixing during their molten state. A comparison of the melt pool geometries between the simulations and experiment were made to validate the model.